“Aplicación del Pensamiento Lean en Proyectos Mediante Lean Project Management” - Campos-Alvarado, Andrés (Instituto Tecnológico de Costa Rica, 2011)
The current of Lean Thinking, and specifically the concepts of Lean Manufacturing, has its origins in the so-called Total Production System (TPS). This system has been defined as a methodology or a philosophy of excellence and continuous improvement, aimed at eliminating waste and activities that do not add value to the processes for manufacturing, distribution and marketing of products or services, increasing the value of each activity carried out and eliminating those activities and sub processes that are not required. In this way, and by Lean, companies reduce costs, improve their processes, eliminate waste, increase customer satisfaction and maintain profit margins. The essence of Lean concepts is to eliminate waste, that is to say, delete everything that does not generate value. The development of this document will highlight how Lean Thinking can contribute to the traditional Project Management, through Lean Project Management, thus achieving a more efficient management of projects.
Proyecto de Graduación (Maestría en Gerencia de Proyectos con énfasis en Gerencia de Proyectos Empresariales) Instituto Tecnológico de Costa Rica. Área Académica de Gerencia de Proyectos, 2011.
Keywords: Calidad; Producción; Comercialización; Costos; Valor; Conocimiento; Herramientas